Power quality improvement using fuzzy logic-based compensation in a hybrid power system - Soumya Ranjan Das; Debani Prasad Mishra; Prakash Kumar Ray; Surender Reddy Salkuti; Arun Kumar Sahoo (Institute of Advanced Engineering and Science, 2021)
This paper is based on the improvement of power quality (PQ) using fuel cell and fuzzy based controller. By using the proposed controller, the quality of power in the grid system especially in micro grid connected with non- linear and unbalanced load is enhanced. The configuration of the system is combined with hybrid arrangement of photovoltaic ([PV) with wind energy conversion system (WECS), fuel cell (FC) including the compressed air energy storage system (CAES) where the power management is controlled by using the distributed power sharing technique. In this proposed system the distortions in voltage at point of common coupling (PCC) is decreased by using the FC which acts as compensator in hybrid system. Reference current is developed which depends on real and reactive power of the source connected to the compensator. Based on demand of power for nonlinear load, without using any external communication interfaces, the proposed control theory can change the modes of operation and can compensate the unbalance in the system which is caused due to single-phase micro sources and load changes. The complete productive design of the micro-sources and power electronic converters are presented in the paper. The operation and performance of the proposed controller used in microgrid is validated through simulation in MATLAB/Simulink environment.